2013
DOI: 10.1080/13540602.2013.848525
|View full text |Cite
|
Sign up to set email alerts
|

The influence of teachers’ interests, personalities and life experiences in intercultural languages teaching

Abstract: This paper reports on a study that investigated teachers' perceptions about the significance of intercultural understanding (IU) in the modern foreign languages (MFL) curriculum. The research was conducted in the wake of a National Curriculum revision in 2007 in England that for the first time listed 'IU' as one of the four key concepts underpinning the study of languages in the Programme of Study. In contrast to other writers who frequently explain MFL teachers' attention to intercultural learning as a conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…In addition to residence abroad, Peiser & Jones (2013) emphasise the significance of the individual teacher's views and philosophies, as does Lázár (2011). Some teachers accept both the communication axiom and the education axiom, but others do not; they say they want to focus only on communication.…”
Section: Research On Teachers In the Cultural Turnmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to residence abroad, Peiser & Jones (2013) emphasise the significance of the individual teacher's views and philosophies, as does Lázár (2011). Some teachers accept both the communication axiom and the education axiom, but others do not; they say they want to focus only on communication.…”
Section: Research On Teachers In the Cultural Turnmentioning
confidence: 97%
“…Other suggestions exist. Peiser & Jones (2013) also recommend that there should be self-analysis using the framework from Kelchterman (2009). There is also Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/22/15 5:01 PM the Autobiography of Intercultural Encounters (AIE) 2 , which provides a means of reflecting on experience and learning the concepts and framework on which it is based, and a second version which focuses on analysing one's own experience of otherness through the visual media.…”
Section: Research On Teachers In the Cultural Turnmentioning
confidence: 99%
“…Intercultural language teaching (see Byram, ; Byram & Zarate, ; Kramsch, ) integrates culture and language, and is described as
teaching skills to critically analyse the ‘other’ (...) in order to be able to view other cultures in a less ethnocentric manner (...) [where] fostering harmonious relationships with people from other cultures should be an explicit purpose of language teaching (...) [and where] cultural and linguistic learning should be closely integrated. (Peiser & Jones, , p. 377)
…”
Section: Teacher Understanding Of Culture In Language Teachingmentioning
confidence: 99%
“…(Peiser & Jones, 2014, p. 377) However, a number of studies have shown that teachers perceive various issues that prevent them from doing intercultural language teaching (e.g., Byram, 1997;Byram & Zarate, 1996;Liddicoat & Crozet, 2000). Studies in the past decade have identified teachers' beliefs about their own lack of personal involvement in the target culture (Sercu et al, 2005;Sercu & St. John, 2007); lack of support, training, and materials (Díaz, 2013;Oranje, 2012;Sercu & St. John, 2007); and lack of practices (Díaz, 2013;Peiser & Jones, 2014). Teachers believe they are stymied by students' lack of sufficient proficiency for intercultural learning (Sercu et al, 2005;Sercu & St. John, 2007), lack of critical ability (Sercu & St. John, 2007), and lack of interest and motivation (Sercu & St. John, 2007).…”
Section: Teacher Understanding Of Culture In Language Teachingmentioning
confidence: 99%
“…[1]. Current psychological literature widely addresses the role of teachers' personal resources [2][3][4][5][6][7], relationships with students [8,9], and individual professional resources [10,11] in managing the mentioned challenges. Despite the meaningful role of the teacher's individual contributions to these issues, collaborative practices and strategies seem to better fit such needs [12,13].…”
Section: Introductionmentioning
confidence: 99%